The Effect of Internal Audit and Internal Control Systems on University Financial Management with the Moderating Role of Stakeholder Engagement - Sahnidar Sahnidar (Utan Kayu Publishing, 2025)
This study aims to examine the effect of Internal Audit (X1) and Internal Control System (X2) on University Financial Management (Y), with Stakeholder Engagement (Z) serving both as an independent variable and a moderating variable. This research employed a quantitative approach using a survey method through a structured questionnaire. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The measurement model results indicate that all indicators meet the required validity and reliability criteria, confirming that the constructs are appropriate for further analysis. The structural model results reveal that Internal Audit (X1) and Internal Control System (X2) do not have a significant effect on University Financial Management (Y). In contrast, Stakeholder Engagement (Z) has a significant effect on Y, although the relationship is negative. Furthermore, the moderation analysis shows that stakeholder engagement does not significantly moderate the relationship between X1 and X2 on Y. The R-square value of 0.225 suggests that the model provides limited explanatory power, indicating that other factors outside the proposed framework may influence university financial management. The findings imply that stakeholder engagement should be managed in a structured and coordinated manner to support effective financial management in higher education institutions